Fiber optic enzymatic biosensors and biosensor arrays for measurement of chlorinated ethenes - Zhong, Zhong, author; Reardon, Kenneth F., advisor; Lear, Kevin, committee member; Dandy, David S., committee member; Henry, Charles S., committee member (Colorado State University. Libraries, 2011)
Chlorinated ethenes such as trichloroethylene (TCE), tetrachloroethylene (PCE), three isomers of dichloroethylene (DCEs) and vinyl chloride (VC) are used as solvents and cleaners in a variety of industrial and commercial areas. Chlorinated ethenes have become one of the most common environmental pollutants in groundwater contamination sites due to their widespread usage, moderate solubility compared with other organic pollutants and recalcitrance to natural attenuation. Fiber optic enzymatic biosensor was developed in this study as a continuous, real time and in situ measurement principle. TOM biosensor, first reported enzymatic biosensor, was initiated with toluene measurement in aqueous solution as proof-of-concept experiments. The subsequent success of TOM and TOM-Green in TCE analysis showed great potential of biosensor measurement for chlorinated ethenes, despite the ubiquitous problem for monooxygenase-based biosensor with NADH consumption overtime and after usage. In addition, epoxide toxicity also increased the difficulty of biosensor application for measurement of chlorinated ethenes, although several TOM-Green transformants could mitigate the toxicity with rapid epxoide degradation. Plasmid transformation with was introduced to manipulate the construction of new TOM and TOM-Green transformants with capability of intracellular NADH regeneration. FDH regeneration system was studied for both TOM and TOM-Green cells, while TOM+FDH showed great activity retention and regeneration ability and TOM-Green+FDH was able to retain activity over prolonged storage but failed on regeneration after repeated usage due to the toxicity of TCE epoxide. Biosensor array was built with pH-based biosensor to measure a group of haloalkanes. The design concept of biosensor array and detection instrumentation was successful. Linear approach in array data analysis was simple and fast but lacked of accuracy, while nonlinear approach increased the complexity of data analysis to a new level with precision in sacrifice of efficiency. Multivariable chemometric approach was also introduced in array data analysis, providing a high-throughput alternative and a means of quantitatively assessing matrix effects. This project demonstrates the potential of fiber optic enzymatic biosensor and biosensor array as measurements for different analyte are described. This is also one of the first comprehensive studies in oxygen-based biosensor and its application and great potential in food, clinical, and environmental monitoring, industrial process control and other related areas.
Keywords: biosensor array; toluene o-monooxygenase; optode; enzyme biosensor